BEST1 novel mutation causes Bestrophinopathies in six families with distinct phenotypic diversity. Issue 1 (15th November 2022) - Yang, Shangying; Li, Zhen; Cheng, Wanyu; Ma, Meijiao; Qi, Rui; Rui, Xue; Ren, Yinghua; Sheng, Xunlun; Rong, Weining
Abstract: Purpose: To report novel BEST1 variants in six Chinese families with bestrophinopathies of two different inheritance modes and analyze the intrafamilial phenotypic diversity. Method: A total of 25 participants including 13 patients and 12 healthy family members from 6 Chinese families with bestrophinopathies were available for genetic and clinical analysis. All of the patients were subjected to comprehensive ophthalmic evaluations and exome sequencing was performed on the probands to detect the causative variants. The pathogenicity of gene variants was predicted using silico analysis and evaluated according to ACMG guidelines. All (likely) pathogenic variants were determined by Sanger sequencing and co‐segregation analyses were performed on available family members. The relevant original literature previously reported was retrieved to explore the relationship between BEST1 ‐related gene variants and clinical features. Results: In the 6 families, 3 families (10 patients) were assigned as autosomal dominant bestrophinopathies (VMD) and 3 families (3 patients) were assigned as Autosomal recessive Bestrophinopathies (ARB). A total of 9 variants on the BEST1 gene were identified, containing 7 missense variants, 1 nonsense variant, and 1 frameshift variant, respectively, of which 3 variants c.88A > G (p.Lys30Glu), c.764G > A (p.Arg255Gln) and c.233dupT (p.Ser79Phefs*153) were novel variants. Three families with ARB were detected with heterozygous variants on the BEST1 gene.2 families (8 patients) with BVMD showed markedly irregular dominant inheritance, and the severity of macular lesions varies greatly among individuals of the same family. Among them, the probands showed typical vitelliform lesions in the macula, while the other six patients had no visible signs of the disease by fundus photography (ophthalmoscopy) and minor lesions could be detected on OCT in two patients, the continuity of the ellipsoidal band was interrupted with the chimeric band. The phenotypes of the patients in the three ARB families ranged from typical/atypical vitelliform lesions to extensive extramacular deposits (peripheral spots). Conclusion: This study provided evidence that the phenotype of BVMD manifested irregular dominant inheritance, with patients carrying a pathogenic heterozygous variant of BEST1 to develop obvious intrafamilial phenotypic diversity, and the patients who harbor two pathogenic alleles showed recessive inheritance bestrophinopathies with distinct phenotypic diversity. Our study also emphasized the importance of comprehensive genetic analysis in patients with bestrophinopathies, and in such challenging families with distinct intrafamilial phenotypic diversity, it shall provide novel insights into phenotypic assessments of bestrophinopathies, and contribute to better diagnosis, prognosis, and treatment for these patients. Abstract : BEST1 novel mutation causes Bestrophinopathies in six families with distinct phenotypic diversity.